Pengaruh Tingkat Pendidikan Terhadap Peluang Keluarga Keluar Dari Kelompok Keluarga Miskin - Wawan Hermawan; Lia Yulianti (FEB Universitas Sultan Ageng Tirtayasa, 2021)
Education is a determining factor in improving the quality of human resources. Increased education has a major influence in improving family welfare and provides a great opportunity to get out of the poverty line. This study aims to calculate the opportunity to increase the education level of the head of household in Indonesia in order to get out of the poor family group. The data used is the March 2020 Susenas with a logistic regression estimation approach. The estimation results show the level of significance for all levels of education, which reduces the chances of families entering the poor family group. Families living in urban areas, male heads of household and increasing age of heads of household, reduce the chances of families entering poverty. In addition, the status of self-employed with assistance provides a reduced opportunity for families to enter poverty.